STRATEGI MANAJEMEN EKSTRAKURIKULER DALAM MEWUJUDKAN BAKAT DAN MINAT SISWA DI KE-JIAN ELEMENTARY SCHOOL, TAIWAN - Sheila Zhulhijjah; Ahmad Abdullah Zawawi (STKIP Pesisir Selatan, 2025)
Objective: This study aims to analyze the management strategies for extracurricular activities in realizing students' talents and interests at Ke-Jian Elementary School, Taoyuan, Taiwan, through the POAC (Planning, Organizing, Actuating, Controlling) management approach. This study uses a qualitative approach with a descriptive design to describe in depth the process of planning, organizing, implementing, and evaluating extracurricular activities implemented in schools. The results show that activity planning is carried out systematically through the identification of student interests and talents, the preparation of annual plans by a special division, and collaboration with external parties such as Yuan Ze University, National Tsing Hua University, and National Chiayi University. In terms of organization, the school implements a clear division of tasks between the principal, permanent teachers, and guest teachers based on their respective expertise. Activities are carried out regularly every week, covering the fields of arts, sports, and science, and even continue during the holidays with the full support of partner institutions at no cost to students. Evaluations are conducted through observation of attendance, discipline, work results, and student participation in various competitions and exhibitions.